2004
DOI: 10.2133/dmpk.19.308
|View full text |Cite
|
Sign up to set email alerts
|

Seven Novel Single Nucleotide Polymorphisms in the Human SLC22A1 Gene Encoding Organic Cation Transporter 1 (OCT1)

Abstract: Twenty genetic variations, including seven novel ones, were found in the human SLC22A1 gene, which encodes organic cation transporter 1, from 116 Japanese individuals. The novel variations were as follows: -94C>A in the 5'-untranslated region (A of the translation start codon is numbered +1 in the cDNA sequence; MPJ6_OC1001), 350C>T (MPJ6_OC1004), IVS1-35T>C (MPJ6_OC1006), 561G>A (MPJ6_OC1010), IVS6+75C>G (MPJ6_OC1014), IVS8+108A>G (MPJ6_OC1017), and 1671_1673delATG (MPJ6_OC1020). The frequencies were 0.082 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 14 publications
3
26
0
1
Order By: Relevance
“…In the OCT1 gene, all non-synonymous variants except 41Phe > Leu and 117Pro > Leu have already been identified in some racial populations, with a frequency of 0.005-0.81 (Kerb et al 2002;Shu et al 2003). The 41Phe > Leu and 117Pro > Leu allele frequencies were relatively low (0.004), and they have already been reported in a Japanese population (Itoda et al 2004). Recent expression studies have indicated that 341Pro > Leu had decreased ability to transport test compounds, while 160Phe > Leu and 408Met > Val were unchanged (Kerb et al 2002;Sakata et al 2003; Predictive accuracy = 55.5% Shu et al 2003).…”
Section: Discussionmentioning
confidence: 83%
“…In the OCT1 gene, all non-synonymous variants except 41Phe > Leu and 117Pro > Leu have already been identified in some racial populations, with a frequency of 0.005-0.81 (Kerb et al 2002;Shu et al 2003). The 41Phe > Leu and 117Pro > Leu allele frequencies were relatively low (0.004), and they have already been reported in a Japanese population (Itoda et al 2004). Recent expression studies have indicated that 341Pro > Leu had decreased ability to transport test compounds, while 160Phe > Leu and 408Met > Val were unchanged (Kerb et al 2002;Sakata et al 2003; Predictive accuracy = 55.5% Shu et al 2003).…”
Section: Discussionmentioning
confidence: 83%
“…Selection of OCT1 and OCT3 variants for genotyping was based on two strategies. All variants associated with functional consequences proven by in vitro/in vivo data [29][30][31][32]36,37 were included as well as variants in the 5Ј and 3Ј regions of the OCT1 and OCT3 genes that were available in the National Center for Biotechnology Information database (dbSNP build 127; http://www. ncbi.nlm.nih.gov/sites/entrez?dbϭsnp).…”
Section: Methodsmentioning
confidence: 99%
“…29 In humans, several OCT1 variants with reduced transport function, including metformin transport, have been identified. [29][30][31][32] Some of these variants were recently associated with a significantly decreased glucose-lowering response to metformin and altered metformin pharmacokinetics in healthy volunteers. 29,33 However, in another study, the prevalence of OCT1 variants did not differ between responders and nonresponders to metformin, 34 which may be due to different ethnic study populations or to a small number of subjects in the latter study.…”
mentioning
confidence: 99%
“…CYP3A5*3 (6986A4G (rs776746)) and SLC22A1 (156T4C (rs1867351), 480G4C (rs683369), 1022C4T (rs2282143) and 1222A4G (rs628031)) genotyping was performed by PCR-RFLP, as previously described by Fukuen et al 34 and Itoda et al, 25 respectively. Similarly, ABCC2 (À24C4T (rs717620)) and ABCB1 (1236T4C (rs1128503), 2677G4T/A (rs2032582) and 3435T4C (rs1045642)) were genotyped as described by Naesens et al, 35 Wu et al, 36 Tanaka et al 37 and Cascorbi et al, 38 respectively.…”
Section: Measurement Of Plasma Im Concentrationmentioning
confidence: 99%
“…[19][20][21] Although IM is a substrate of OCT1, 15,22,23 no association between IM and SLC22A1 286C4T or 1498G4A, variants not common in the Japanese population, was previously observed. 24,25 In addition, in vitro studies have shown that organic anion-transporting polypeptide 1B3 (OATP1B3), which is encoded by SLCO1B3, contributes to IM uptake into hepatocytes. 24 However, to date, the influence of SLCO1B3 SNPs on the pharmacokinetics of IM has not been reported.…”
Section: Introductionmentioning
confidence: 99%